Case Report: An unusual case of wide ileoileal intussusception associated with intestinal volvulus in a 8-months-old infant - Romano, Giorgia; Frediani, Simone; Aloi, Ivan Pietro; Bertocchini, Arianna; Pardi, Valerio; Accinni, Antonella; Inserra, Alessandro (Frontiers in Pediatrics, 2024)
Introduction: Midgut volvulus and intussusception are prevalent paediatric abdominal emergencies. To the best of our knowledge, this is the first reported case of a connection between intestinal volvulus and a massive intussusception.Case Report: An 8-month-old male infant was brought to the emergency room with a history of abdominal pain and vomiting for <24 h. On physical examination, the child appeared restless and was found to have a circumferential hard mass of approximately 4 cm in diameter in the epigastric region. Upon admission, laboratory results showed a C-reactive protein level of 0.4 mg/dl, LDH level of 351 U/L, mild leukocytosis with a white blood cell count of 12 x 103/µL, and 67% neutrophils. A physical exam was significant for abdominal distention, hyperresonance in percussion, and a palpable, painful epigastric mass. The findings of the operation included a dilated and ischemic intestinal loop, approximately 25 cm from the ileocecal valve, twisted upon itself for three turns. After de-rotation, an extensive occluding ileo-ileal invagination with an ischemic intestinal loop was identified, and a length of approximately 55-60 cm of the distal ileum, including the ischemic segment, was resected.Discussion: This is the first reported case of a connection between intestinal volvulus and a massive intussusception. Currently, only two reported cases describe the connection between volvulus and intussusception, which are insufficient to establish a direct link between the two clinical conditions.